Passenger head kinematics in abrupt braking and lane change events. (21st March 2018) - Reed, Matthew P.; Ebert, Sheila M.; Jones, Monica L. H.; Park, B.-K. Daniel; Hallman, Jason J.; Sherony, Rini
Abstract: Objective: A test track study was conducted to quantify patterns of adult front seat passenger head motion during abrupt vehicle maneuvers. Method: Eighty-seven men and women with a wide range of body sizes and ages participated in data collection on a closed test track in a passenger sedan under manual control by a test driver. Because a primary goal of the study was to gather "unaware" data, the participants were instructed that the study was concerned with vehicle dynamics and they were required to read from a questionnaire taped to the top of their thighs as the drive began. The first event was a hard brake (approximately 1 g ) to a stop from 35 mph (56 kph). Within the space of approximately 5 min the participants also experienced an aggressive lane change, a sharp right turn with simultaneous hard braking, and a second hard braking event. A Microsoft Kinect v2 sensor was positioned to view the area around the front passenger seat. Head location was tracked using the Kinect data with a novel methodology that fit 3D head scan data to the depth data acquired in the vehicle. Result: The mean (standard deviation) forward excursion of the estimated head center of gravity (CG) location in the first braking event was 135 (62) mm. The forward head CG excursion in the second braking event of 115 (51) mm was significantly less than that in the first, but the difference was small relative to the within-condition variance. Head excursion on the second braking trial was less than that on the first trial for 69% of participants. The mean maximum inboard head excursion in lane-change maneuvers was 118 (40) mm. Forward head excursions in braking were significantly smaller for older passengers and those with higher body mass index, but the combined factors accounted for less than 25% of the variance. Inboard head excursion in the lane-change event was significantly related to stature, but only about 7% of variance was related to body size. Head excursions for men and women did not differ significantly after accounting for body size. Discussion: This is the first quantitative occupant dynamics study to use a large, diverse sample of passengers, enabling the exploration of the effects of covariates such as age and body size. Conclusions: The data demonstrate that a relatively large range of head positions can be expected to result from abrupt vehicle maneuvers. The data do not support simple scaling of excursions based on body size.